Clinical impact of videocapsule and double balloon enteroscopy on small bowel bleeding: Results from a large monocentric cohort in the last 19 years. Issue 2 (February 2022) - Elli, Luca; Scaramella, Lucia; Tontini, Gian Eugenio; Topa, Matilde; Conte, Dario; Sidhu, Reena; Rondonotti, Emanuele; Penagini, Roberto; Vecchi, Maurizio
Abstract: Background: Suspected small bowel bleeding (SSBB) is the main indication for videocapsule endoscopy (VCE) and double balloon enteroscopy (DBE). We assessed the impact of both modalities in a large cohort of SSBB patients in a European tertiary center. Methods: We retrospectively evaluated consecutive patients with SSBB undergoing VCE and/or DBE from March 2001 to July 2020. Demographic/clinical parameters, anticoagulant therapies, technical characteristics and adverse events were collected, as well as diagnostic yield (DY), VCE–DBE concordance, hemoglobin (Hb) values before and after DBE, and complications. Results: 807 VCEs and 407 DBEs were performed in 751 patients. The DY was significantly higher in DBE compared with VCE (68.8% vs 57.7%), with the highest (75%) yield for overt active SB bleeding. The agreement between VCE and DBE was generally suboptimal ( k  = 0.059). This improved in cases where both procedures were done within 1–5 days of the other ( k  = 0.323). Post-procedural Hb values were significantly higher. In patients treated with direct oral anticoagulants (DOACs), there were no differences in DY, complications or Hb values compared with non-DOAC patients. Conclusion: VCE and DBE play a pivotal role in the diagnostic and therapeutic approach to SSBB, having a high clinical impact even in patients treated with DOACs.